Pemanfaatan Google Formulir Sebagai Sistem Pendaftaran Anggota Pada Website Asosiasi - Untung Rahardja; Ninda Lutfiani; Mochamad Sandi Alpansuri (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2018)
Indonesian private university associations still use conventional system. this can be seen there is no registration of members online and registration work and this data collection is still using file system in the form of printout form. Then performed a system of checking and inputting data. If there is an error in charging the data, then do the system repetition. Things like this are deemed very ineffective because it will cause the buildup of files. This process is the one that until now runs in the association of Indonesian private universities. Therefore, Indonesian private university associations utilize google forms to support member registration activities online on the website of Indonesian private college association. Google form is a form facility that can be used to get the data of someone either in the form of questionnaire or registration, provided google platform which can easily be used for free in Google Drive. By making observations in the form of data collection, by doing a direct observation of an existing problem, it is considered less effective and efficient in managing a member report conducted conventionally through several convoluted processes and tend to require a long time so it is less effective. So that the need for a conventional system to be online so that with the online registration is aimed to improve the effective and efficient workers in managing data collection and registration of members previously done conventionally at the association of Indonesian private universities.